2012
DOI: 10.1016/j.celrep.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Stoichiometry of the GluK2/GluK5 Kainate Receptor Complex

Abstract: Ionotropic glutamate receptors assemble as homo- or heterotetramers. One well-studied heteromeric complex is formed by the kainate receptor subunits GluK2 and GluK5. Retention motifs prevent trafficking of GluK5 homomers to the plasma membrane, but co-assembly with GluK2 yields functional heteromeric receptors. Additional control over GluK2/GluK5 assembly seems to be exerted by the amino-terminal domains, which preferentially assemble into heterodimers as isolated domains. However, the stoichiometry of the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 36 publications
4
41
1
Order By: Relevance
“…S1 and S2). This probability value of mEGFP being fluorescent is similar to what was observed previously for mEGFP fused to a number of other membrane proteins (28)(29)(30)(31)(32)(33). Binomial predictions based on four subunits also accounted well for the other hBest family members ( Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…S1 and S2). This probability value of mEGFP being fluorescent is similar to what was observed previously for mEGFP fused to a number of other membrane proteins (28)(29)(30)(31)(32)(33). Binomial predictions based on four subunits also accounted well for the other hBest family members ( Fig.…”
Section: Resultssupporting
confidence: 70%
“…Although earlier biochemical studies concluded that the Best1 channel is an oligomer, the estimate of the number of subunits ranged from 2 to 5 (22,27). To resolve this question, we used the single-molecule subunitcounting method (28)(29)(30)(31)(32)(33) to determine the number of subunits by counting the number of fluorescence-bleaching steps of monomeric enhanced green fluorescent protein (mEGFP)-tagged hBest1 in Xenopus oocytes [EGFP-tagged hBest1 was previously shown to be functional (34)]. The main advantages of this method are that: (i) the counting uses Total Internal Reflection Fluorescence Microscopy (TIRFM) to focus exclusively on functional channels in their native physiological environment, the plasma membrane of live cells, and (ii) because the level of expression can be easily controlled in oocytes, it is possible to obtain low enough densities so that each channel appears as an individual fluorescent spot that can be readily resolved from its neighbors.…”
Section: Resultsmentioning
confidence: 99%
“…Like STEPFINDER, PIF could also be applied in the context of molecular motor displacements or similar experiments, especially because blinking would not be an issue. Similarly, PIF could also analyze data derived from oocytes or even purified proteins (7,14,15,18).…”
Section: Discussionmentioning
confidence: 99%
“…To take this issue into account, stoichiometry can be determined by studying protein complexes at the single molecule level either with atomic force microscopy (5) or fluorescence spectroscopy (6 -11). In particular, the single subunit counting technique has proven to be a powerful tool (7,(11)(12)(13)(14)(15)(16)(17)(18). For this technique, each subunit is first tagged with a fluorescent marker and then viewed by total internal reflection fluorescence (TIRF) 6 microscopy that limits background noise in favor of signals coming from the plasma membrane (19).…”
mentioning
confidence: 99%
“…We therefore assessed the effect of 14-3-3 on the kinetics of receptors formed by GluK2a/GluK5 heteromers. In heterologous cells, cotransfection of GluK2a and GluK5 cDNAs at an appropriate ratio is expected to yield surface expression of functional GluK2a/GluK5 heteromeric receptors (41,50). However, the amplitude of heteromeric GluK2a/GluK5 receptor currents is considerably smaller than that of homomeric GluK2a receptors (41).…”
Section: Effect Of 14-3-3 On Desensitization Kinetics Of Gluk2a-contamentioning
confidence: 99%